Informal finance and poverty alleviation : a grassroots study of small farmers' credit in West Sumatra, Indonesia : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Fitri, Resfa (Massey University, 2006)
The main objective of this study is to explore the credit and savings behaviour of small farmers in rural areas of Indonesia, with particular reference to informal systems of credit. It examines the relationship between credit and rural poverty and on identifying small farmers' credit and savings behaviour as well as problems they encounter in accessing credit programmes at the grassroots level. In this study, the extent of informal credit programmes in rural areas is identified and an assessment is made of how important these schemes are to rural people, especially small farmers, from economic, social and cultural points of view. The influence of local culture and values on informal rural credit systems is also examined. Fieldwork was conducted in three villages of Solok district, West Sumatra, Indonesia. This study reveals that credit programmes, whether from the formal or informal sectors, have not had a positive impact on poverty alleviation. The majority of formal credit programmes in the three case study villages failed to give service to the rural poor, especially small farmers. It is likely that the reason for the failure was the unmet demand between the formal financial institutions as the credit providers and the small farmers as the credit recipients. The informal credit programmes were also unsuccessful in helping the poor to increase their income because the loans were small in size and were mainly used for fulfilling basic and emergency needs. Credit from informal sources is used for survival rather than for development. However, informal credit schemes were favoured by the majority of the rural population due to their flexibility and adaptation to local cultures and values. This study finds that informal credit schemes in these three case study villages have potential to empower local people and to strengthen traditional rural credit systems in the era of decentralisation. Arisan Suku, Julo-julo and 'friendly moneylenders' are examples of these informal credit schemes, and they figured significantly in the credit and savings activities of the poor in the study area. Therefore, this study rejects the conventional assumptions that informal finance is exploitative, insignificant and unorganised. The positive impact of local culture and values on the informal credit systems in the study area mainly focuses on the influence of local culture of Minangkabau and the value of Islamic religion in shaping rural informal credit systems. In this case Minangkabau people have been practicing credit and savings activities for a long time, and this reinforces the informal credit system in the area. Regarding the influence of Islamic values, this is in line with the current growing attention paid to the Islamic finance system, both at national and international levels. The positive impacts of local culture and values are important for developing a more participatory rural financial system. This study recommends that the future rural financial systems can be developed by combining positive features of both formal and informal credit systems.
Keywords: Rural poverty; Small farmers; Credit systems; Fields of Research::370000 Studies in Human Society